Genetic counseling in industry settings: Opportunities in the era of precision health. Issue 1 (19th April 2018) - McWalter, Kirsty; Cho, Megan T.; Hart, Tara; Nusbaum, Rachel; Sebold, Courtney; Knapke, Sara; Klein, Rachel; Friedman, Bethany; Willaert, Rebecca; Singleton, Amanda; Williams, Leah; Butler, Elizabeth; et al.
Abstract : The skill sets of genetic counselors are strongly utilized in industry, as evidenced by 20% of genetic counselors reporting employment within industry in 2016. In addition, industry genetic counselors are expanding their roles, taking on new responsibilities, and creating new opportunities. These advances have impacted the profession as a whole including, but not limited to, genetic counseling training curricula, a shift back to genetic counseling directly to patients, and a growing influence of genetic counselors on industry test offerings. Industry genetic counselors and training programs are working together to address the challenges and opportunities presented by workforce changes and novel interpretations of how genetic counselors' core competencies can be utilized. Counseling of patients by industry genetic counselors has become more commonplace and addresses a need for alternate service delivery models. Industry genetic counselors often provide significant contributions to test development, education, marketing, and interpretation. Beyond these broad examples, individual industry genetic counselors have created unique niches for themselves, using their genetic counseling training combined with unique opportunities offered through industry, as illustrated by genetic counselors' various roles and responsibilities highlighted here.